Hubungan Pengetahuan Terhadap Tingkat Kepatuhan Minum Obat Anti Hipertensi - dewi winni fauziah; Elly Mulyani (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Hypertension is a condition where an increase in systolic or diastolic blood pressure ≥ 140/90 mmHg. Success of hypertension therapy is influenced by several factors, one of which is compliance with taking hypertension medication. Adherence to take medication is very important to improve the effectiveness of treatment and prevent complications. Poor adherence to drug consumption is the most frequent cause of failure of antihypertensive therapy. Compliance can be used as a parameter of a patient's level of knowledge in carrying out instructions from medical personnel. The purpose of this study was to determine the relationship of knowledge of adherence to taking antihypertensive drugs for patients in the work area of the Lebong District Health Center in 2019. The research method used in this study is analytical research using a cross-sectional design which is a research plan of a study to study the dynamics of the correlation between the independent variable (knowledge) with the effect or dependent variable (the level of compliance taking antihypertensive medication) which is observed or collected data at once at the same time. From this study obtained the Odds Ratio (OR) = 3,781 (95% CI: 1,503-9,513) which means someone with less knowledge has a risk of 1.503 times for not compliant to take anti-hypertensive drugs than someone who has good knowledge. There is a significant relationship between knowledge with the level of adherence to take antihypertensive medication in the working area of the Lebong District Health Center.